2017
DOI: 10.1080/08869634.2017.1362786
|View full text |Cite
|
Sign up to set email alerts
|

A digital poll of dentists testing the accuracy of paper mark subjective interpretation

Abstract: The mean correct response was a mere 13.13% correct (86.87% incorrect). Random chance was calculated at 16.7% correct. The cuspid contacts were the least often chosen as the most forceful contact. The Mann-Whitney U test found a significant difference between choosing the anterior teeth vs. posterior teeth. onclusions: Subjective interpretation is an inaccurate method for determining high force occlusal contacts. The reported low correct percentage fell below random chance, suggesting that dentists are unable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 14 publications
0
10
0
5
Order By: Relevance
“…O método do papel articular, apesar de ser o mais empregado para a checagem dos contatos oclusais 6,2,13 , marca apenas a localização e o tamanho dos contatos, não servindo para a quantificação das forças oclusais aplicadas, o número de contatos e a sua sequência 6,14 . É possível, ainda, correlacionar o tamanho da área marcada com a carga aplicada, porém, tal associação pode gerar um falso positivo 6 .…”
Section:  Sentido Mésiodistalunclassified
See 1 more Smart Citation
“…O método do papel articular, apesar de ser o mais empregado para a checagem dos contatos oclusais 6,2,13 , marca apenas a localização e o tamanho dos contatos, não servindo para a quantificação das forças oclusais aplicadas, o número de contatos e a sua sequência 6,14 . É possível, ainda, correlacionar o tamanho da área marcada com a carga aplicada, porém, tal associação pode gerar um falso positivo 6 .…”
Section:  Sentido Mésiodistalunclassified
“…A interpretação dos contatos oclusais é realizada de forma subjetiva, sendo assim, as marcas de coloração mais intensa representam os contatos fortes, enquanto que as marcas de cor mais fraca correspondem aos contatos leves, porém, esse método carrega consigo grande propensão ao erro 14 .…”
Section:  Sentido Mésiodistalunclassified
“…The T-scan 10 is an innovative technology, that records in real-time the contact force distribution as it changes functionally from 1st contact through until complete Maximum Intercuspation (MIP). This method has been proven precise and reproducible (17), while eliminating the clinician subjectivity of occlusal paper mark interpretation (18)(19)(20)(21)(22) or shim stock removal "feel". The T-Scan overrides the limitations of waxes and silicone impressions techniques that are static, as it accurately quanti es many differing relative occlusal contact force parameters and contact timing sequence durations for clinical occlusal diagnosis and treatment, that can be statistically analyzed (23).…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggested that long‐standing controversies about occlusal mark interpretations are focused on artefactual observations, and are not scientific in nature. This has been confirmed in other studies where clinician occlusal force perceptions drawn from how the ink markings appear visually correlates very poorly with the actual occlusal force present in different sized markings …”
mentioning
confidence: 99%
“…However, the study’s Conclusions presented in the Abstract are misleading to the reader with respect to the T‐Scan sensor, specifically; “…popular occlusal detection products alter the occlusal contact forces, and therefore, their markings cannot characterize the actual occlusion. ” This statement only applies to the tested marking materials, because although the T‐Scan sensor does alter the load moments of the casts (like all the interocclusal indicators tested by the authors), the T‐Scan does not “characterize occlusion” by marking the teeth with ink smears, which are then poorly subjectively observed by clinicians . So to suggest that because the T‐Scan sensor sits between the teeth (while not marking them with ink), it is unable to “characterize occlusion,” is a completely false representation of the T‐Scan sensor’s true occlusal force and timing measurement capabilities.…”
mentioning
confidence: 99%